A comparison of trunk and shank angles between elite and sub-elite sprinters during sprint acceleration - Donaldson, B. J.; Bayne, H.; Bezodis, N. E. (ISBS Proceedings Archive (Michigan), 2020)
Acceleration is a movement that requires skilful positioning of the body to apply force in the desired direction. The sagittal plane orientation of the trunk and shank are features that coaches use to visually assess sprint acceleration technique. This study examined differences in trunk and shank angles between elite and sub-elite sprinters during early acceleration using inertial sensors. Elite sprinters exhibited more vertical trunk positions throughout all four steps compared to sub-elite with moderate to very large differences at discrete events (d = 0.79 - 2.16). Shank angles were more vertical at touchdown in sub-elite compared to elite sprinters (d = -0.70 - -0.39), but similar at toe-off. These results suggest that less horizontal trunk lean during acceleration is a feature of higher level sprinters, coaches should be conscious of this when giving technical feedback.